Expanded methods for geometric location of 2D bone histology co-registration in 3D radiology volumes - Jaime Uy De Baron; Robert Phillips; Anthony Butler (Physical and Engineering Sciences in Medicine, 2026)
Bone sarcoma treatment employs wide surgical margins to ensure complete tumour excision, sometimes at the expense of patient quality of life. As precision technologies advance, quantitative data to inform the planned accuracy of surgical margins is increasingly important. This study assesses two novel computational methods (M2, M3) to support the co-registration of 2D histologic images within 3D radiological volumes. Replicated evaluation of an established method (M1) is also performed with new data. M2 suits concave bisected sections by assuming a different orientation during tissue bandsaw than M1. M3 handles freeform geometries by using a third measurement to constrain 2D histology images within 3D space without need for geometric bandsaw assumptions. Three computed distances across 38 canine specimen dissections from each method were compared with three corresponding physical measurements collected during laboratory processing. M1 produced a mean error of 0.12 (± 1.7) mm, M2 produced a mean error of 0.06 (± 1.9) mm, while M3 produced a mean error of 0.02 (± 1.5) mm. Mean errors for each method were of similar magnitude to 3D registration error reported in histology co-registration frameworks for other tissues. This study supports a simple low cost opportunity for use of digital histology images to support bone sarcoma radiology interpretation and treatment planning.

From pixels to patterns: Coupling Optical Coherence Tomography and machine learning for monitoring coastal wetland root systems - Mohamed O. Hassan; Aramy Truong; Maruti Mudunuru; Leslie G. Butler; Andre Rovai; Curtis Larimer; Joseph Daddona; Amir H. Ahkami; Jay Bardhan; Tamas Varga; Kelly Stratton; Satish Karra; et al. (Science of The Total Environment, 2025)

Are geological description practices and classification schemes fit for future use? Breccias as an example - Stephanie Flude; Clare E. Bond; Robert W.H. Butler (Earth-Science Reviews, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Multi-layers: Do incompetent horizons always act as thrust flats? - Clare E. Bond; Francisca Robledo; Robert W.H. Butler (Journal of Structural Geology, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Effects of maternal contact and positive human contact during lactation on pork quality: Positive human contact to piglets during lactation improves pork loin muscle pH - Katelyn Tomas; Jemma Savaglia; Robert J.E. Hewitt; Kate J. Plush; Darryl N. D'Souza; Kym L. Butler; Paul H. Hemsworth; Alan J. Tilbrook (Meat Science, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ramps first – Interpreting thrust nucleation in multilayers - Phoebe R. Sleath; Clare E. Bond; Robert W.H. Butler (Journal of Structural Geology, 2024)

Influence of subtle inherited basement structures on thin-skinned thrust systems: The Caledonian Thrust Front in Lapland (CaTFLap) - Taija Torvela; Robert W.H. Butler (Journal of Structural Geology, 2024)

Mapping faults in 3D seismic data – why the method matters - Francisca Robledo Carvajal; Robert W.H. Butler; Clare E. Bond (Journal of Structural Geology, 2023)

Scale dependency in fish beta diversity–hydrology linkages in lowland rivers - Robert J. Rolls; Ben Wolfenden; Jani Heino; Gavin L. Butler; Jason D. Thiem (Journal of Biogeography, 2023)
Aim A key aspect of biodiversity research is to determine the environmental drivers affecting the degree to which ecological assemblages vary in space (beta diversity). The strength and significance of environmental drivers of beta diversity is, however, influenced by the spatial extent over which beta diversity is assessed. Beta diversity of riverine biota is affected by flow variability. We examined hydrology–beta diversity relationships at two spatial extents (reaches vs. entire systems) within rivers to determine if relationships with hydrological variables are scale dependent or generalisable across spatial scales. Location Murray–Darling Basin, Australia. Taxon Freshwater fish. Methods Fish assemblage data were sourced from two monitoring programmes that sampled sites annually during 2014–2019 and spanned either reaches ( 1000 km) of five tributaries. Beta diversity was examined by calculating pairwise (incidence and abundance) dissimilarities for each year to compare temporal trends in beta diversity. Multi‐site dissimilarities were modelled against hydrological variables using beta regression. Results Inter‐annual change in assemblage composition was detected only at the extent of river reaches but not at the extent of river systems. Temporal variation in within‐river beta diversity showed inconsistent patterns when compared between the two spatial extents. Within‐river beta diversity relationships with hydrological gradients were inconsistent among rivers. Overall, statistical models explained much more variation in within‐river beta diversity when assessed at the reach extent when compared to broader river system extents. Main Conclusions Our findings highlight that changes in within‐river beta diversity are likely to depend on the spatial extent of sampling. Furthermore, inconsistent beta diversity–hydrology relationships among rivers suggest that both empirical evidence and theoretical predictions adopted in ecohydrology may not be transferable among river systems.

A craton-wide geochemical study of Neoarchaean carbonate rocks of Zimbabwe - Axel Hofmann; Robert Bolhar; Anton B. Kuznetsov; Jaganmoy Jodder; Mike Butler; Ai Nguyen (Chemical Geology, 2023)

Assessing Public Preferences of Landscape and Landscape Attributes: a Case Study of the Proposed Appalachian Geopark Project in West Virginia, USA - Ganga Nakarmi; Michael P. Strager; Charles Yuill; Jasmine C. Moreira; Robert C. Burns; Peter Butler (Geoheritage, 2023)

Landscape Characterization and Assessment of a Proposed Appalachian Geopark Project in West Virginia, United States - Ganga Nakarmi; Michael P. Strager; Charles Yuill; Jasmine C. Moreira; Robert C. Burns; Peter Butler (Geoheritage, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

The impact of long-term land leases on farm investment: Evidence from the Irish dairy sector - Tracy Bradfield; Robert Butler; Emma J. Dillon; Thia Hennessy; Jason Loughrey (Land Use Policy, 2023)

Attachment to land and its downfalls: Can policy encourage land mobility? - Tracy Bradfield; Robert Butler; Emma J. Dillon; Thia Hennessy; Jason Loughrey (Journal of Rural Studies, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An Optical Imaging System for Capturing Images in Low-Light Aquatic Habitats Using Only Ambient Light - Camille Pagniello; Jack Butler; Annie Rosen; Addison Sherwood; Paul Roberts; Edward Parnell; Jules Jaffe; Ana Širović (Oceanography, 2021)
It is preferable that methods for monitoring fish behavior, diversity, and abundance be noninvasive to avoid potential bias. Optical imaging facilitates the noninvasive monitoring of underwater environments and is best conducted without the use of artificial lighting. Here, we describe a custom-designed optical imaging system that utilizes a consumer-grade camera to capture images in situ in ambient light. This diver-deployed system can be used to collect time series of occurrences of animals while concurrently obtaining behavioral observations for two weeks to a month (depending on the sampling rate). It has also been configured to be paired with a passive acoustic system to record time-synchronized image and acoustic data. The system was deployed in a protected kelp forest off southern California and captured >1,500 high-quality images per day over 14 days. The images revealed numerous fish species exhibiting biologically important behaviors as well as daily patterns of presence/absence. The optical imaging system is a cost-effective tool that can be easily fabricated and improves upon many of the limitations of previous systems, including deployment length and image quality in low-light and limited-visibility conditions. The system provides a relatively noninvasive way to monitor shallow marine habitats, including protected areas, and can augment traditional survey methods by providing nearly continuous observations and thus yield increased statistical power.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Evaluating Relationships Between Total Dissolved Solids (TDS) and Total Suspended Solids (TSS) in a Mining-Influenced Watershed - Barbara A. Butler; Robert G. Ford (Mine Water and the Environment, 2018)

Cancer in populations of African Ancestry: studies of the African Caribbean Cancer Consortium - Camille Ragin; Elizabeth Blackman; Robin Roberts; Raleigh Butler; Samuel Gathere; Darron Halliday; Kimlin Ashing (Cancer Causes & Control, 2017)

Lack of alarm calls in a gregarious bird: models and videos of predators prompt alarm responses but no alarm calls by zebra finches - Nicole E. Butler; Robert D. Magrath; Richard A. Peters (Behavioral Ecology and Sociobiology, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Isolation and characterization of an interactive culture of two Paenibacillus species with moderately thermophilic desulfurization ability - Jia Wang; Batzaya Davaadelger; Joelle K. Salazar; Robert R. Butler; Jean-François Pombert; John J. Kilbane; Benjamin C. Stark (Biotechnology Letters, 2015)

Quantifying Florida Bay Habitat Suitability for Fishes and Invertebrates Under Climate Change Scenarios - Kelly A. Kearney; Mark Butler; Robert Glazer; Christopher R. Kelble; Joseph E. Serafy; Erik Stabenau (Environmental Management, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Standardized capture rates of the endangered American burying beetle, Nicrophorus americanus Olivier (Coleoptera: Silphidae) using different trap protocols - Stephanie R. Butler; Robert Harms; Kerri Farnsworth-Hoback; Keith Koupal; Jessica Jurzenski; W. Wyatt Hoback (Journal of Insect Conservation, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Relationship between pancreatic vesicular monoamine transporter 2 (VMAT2) and insulin expression in human pancreas - Yoshifumi Saisho; Paul E. Harris; Alexandra E. Butler; Ryan Galasso; Tatyana Gurlo; Robert A. Rizza; Peter C. Butler (Journal of Molecular Histology, 2008)

Menstrual risk factors and early-onset breast cancer - Lesley M. Butler; Nancy A. Potischman; Beth Newman; Robert C. Millikan; Donna Brogan; Marilie D. Gammon; Christine A. Swanson; Louise A. Brinton (Cancer Causes & Control, 2000)

Rapid Communication: Climatic Control on Eutrophication of the Hudson River Estuary - Robert W. Howarth; Dennis P. Swaney; Thomas J. Butler; Roxanne Marino (Ecosystems, 2000)

Time and space variability of «thin-skinned» and «thick-skinned» thrust tectonics in the Apennines (Italy) - Robert W. H. Butler; Sveva Corrado; Stefano Mazzoli; Mauro De Donatis; Daniela Di Bucci; Giuseppe Naso; Davide Scrocca; Carlo Nicolai; Vittorio Zucconi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2000)

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

A novel approach for estimating ecosystem production and respiration in estuaries: Application to the oligohaline and mesohaline Hudson River - Dennis P. Swaney; Robert W. Howarth; Thomas J. Butler (Limnology and Oceanography, 1999)
Most estimates of metabolism in estuaries are based on water samples incubated in bottles. Such approaches may severely underestimate rates of both gross primary production (GPP) and respiration for a variety of reasons, including reduced turbulence, unnatural light fields, respiration of 14 C‐labeled organic matter, and altered grazer communities. These problems may be particularly intense in turbid and deeply mixed estuaries. The measurement of metabolism from in situ changes in dissolved oxygen (DO) concentration over a diel time period offers a potential solution to these problems, but complicated patterns of water advection and mixing in estuaries have limited the use of such open‐water approaches. Here, we describe a method of using diel changes in oxygen concentrations in the oligohaline and mesohaline Hudson River estuary to estimate GPP, whole‐ecosystem respiration (ER), and net ecosystem production (NEP). For this approach, concentrations of DO at any given time for several stations are described as a function of salinity and depth, providing a surface in the three‐dimensional space of oxygen, depth, and salinity. The change in this “response surface” for oxygen over time, once corrected for atmospheric exchange, allows the estimation of metabolism rates. The regression procedures used allow an estimate of the standard error associated with the metabolism measures. For the mesohaline Hudson River estuary, these standard errors are reasonably small. Similarly, any potential errors associated with the estimation of atmospheric exchange in oxygen are small for the Hudson. The technique should be useful for estimating GPP, NEP, and ER in other partially mixed estuaries without the biases associated with incubations in bottles.

On the mechanism of action of thiamin enzymes, Crystal structure of 2-(α-hydroxyethyl)thiamin pyrophosphate (HETPP). Complexes of HETPP with zinc(II) and cadmium(II) - Gerasimos Malandrinos; Maria Louloudi; Cristiana A. Mitsopoulou; Ian S. Butler; Robert Bau; N. Hadjiliadis (JBIC Journal of Biological Inorganic Chemistry, 1998)

Conservation Genetics of North American Freshwater Mussels Amblema and Megalonaias - Margaret Mulvey; Charles Lydeard; Debra L. Pyer; Kimberly M. Hicks; Jayne Brim‐Box; James D. Williams; Robert S. Butler (Conservation Biology, 1997)
Freshwater bivalves are among the most endangered groups of organisms in North America. Efforts to protect the declining mussel fauna are confounded by ambiguities associated with recognition of distinct evolutionary entities or species. This, in part, is due to the paucity of reliable morphological characters for differentiating taxa. We have employed allozymes and DNA sequence data to search for diagnosably distinct evolutionary entities within two problematic genera of unionid mussels, Amblema and Megalonaias. Within the genus Amblema three species are recognized based on our DNA sequence data for the mitochondrial 16S rRNA and allozyme data (Amblema neislerii, A. plicata, and A. elliotti). Only one taxonomically distinct entity is recognized within the genus Megalonaias—M. nervosa. Megalonaias boykiniana of the Apalachicolan Region is not diagnosable and does not warrant specific taxonomic status. Interestingly, Megalonaias from west of the Mississippi River, including the Mississippi, exhibited an allozyme and mtDNA haplotype frequency shift suggestive of an east‐west dichotomy. The results of this study eliminate one subspecies of Amblema and increase the range of A. plicata. This should not affect the conservation status of “currently stable” assigned to A. plicata by Williams et al. (1993). The conservation status of A. elliotti needs to be reexamined because its distribution appears to be limited to the Coosa River System in Alabama and Georgia.

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)